Immune-Intrinsic Myd88 Directs the Production of Antibodies With Specificity for Extracellular Matrix Components in Primary Sjögren’s Syndrome - Kiripolsky, Jeremy; Kasperek, Eileen M.; Zhu, Chengsong; Li, Quan-Zhen; Wang, Jia; Yu, Guan; Kramer, Jill M. (Frontiers in Immunology, 2021)
Primary Sjogren’s syndrome is an autoimmune disease that is predominantly seen in women. The disease is characterized by exocrine gland dysfunction in combination with serious systemic manifestations. At present, the causes of pSS are poorly understood. Pulmonary and renal inflammation are observed in pSS mice, reminiscent of a subset of pSS patients. A growing body of evidence indicates that inflammation mediated by Damage-Associated Molecular Patterns (DAMPs) contributes to autoimmunity, although this is not well-studied in pSS. Degraded extracellular matrix (ECM) constituents can serve as DAMPs by binding pattern-recognition receptors and activating Myd88-dependent signaling cascades, thereby exacerbating and perpetuating inflammatory cascades. The ECM components biglycan (Bgn) and decorin (Dcn) mediate sterile inflammation and both are implicated in autoimmunity. The objective of this study was to determine whether these ECM components and anti-ECM antibodies are altered in a pSS mouse model, and whether this is dependent on Myd88 activation in immune cells. Circulating levels of Bgn and Dcn were similar among pSS mice and controls and tissue expression studies revealed pSS mice had robust expression of both Bgn and Dcn in the saliva, salivary tissue, lung and kidney. Sera from pSS mice displayed increased levels of autoantibodies directed against ECM components when compared to healthy controls. Further studies using sera derived from conditional knockout pSS mice demonstrated that generation of these autoantibodies relies, at least in part, on Myd88 expression in the hematopoietic compartment. Thus, this study demonstrates that ECM degradation may represent a novel source of chronic B cell activation in the context of pSS.